The Process of Development Community Market Driving Mechanism for Strengthenning The Community Economy, Taladkhae Subdistrict Municipality, Nonsong District, Nakhonratchasima Province - Boonsang , Sirikorn; Wongkalasin, Sakul (Journal of Human and Society, Sisaket Rajabhat University, 2025)
This research aimed to: 1) to develop the identity and strategy plan for the community market of Taladkhae Municipality; 2) to analyze stakeholders and their participation in driving the Taladkhae community market; 3) to develop mechanisms and roles in market mobilization; and 4) to synthesize the development process of driving mechanisms to strengthen the community economy of Taladkhae Municipality. This study employed a community-based research (CBR) approach and integrated participatory action research (PAR) techniques. Research tools included focus group discussions, in-depth interviews, document analysis, and participatory workshops. Data were analyzed using causal analysis methods. The findings revealed that: 1) In the past, the Taladkhae community market was the place for employment and making income for the community due to its location at a three-way junction and function as a rest stop, resulting in a high concentration of shops and services. However, the expansion of the road into four lanes led to a significant decline in market depression. To revitalize the market, its identity was redefined as a “community lifestyle market” focused on safe, affordable, high-quality local products under the brand name "Taladkhae Care Khun." The landscape was redesigned, and a logo featuring the Kae flower was created to reflect the community’s traditional character. A strategic development plan was formulated, encompassing the definition of market vision and identity, the promotion of local products, landscape improvement, and enhancement of the market management system. 2) Stakeholders within the community include community leaders, occupational groups, and local shop owners. External stakeholders include the Taladkhae Municipality, local government agencies, Nakhon Ratchasima Rajabhat University, and passing motorists and travelers. 3) The mechanism of market driving was established through a committee structure with designated roles and responsibilities, including management and operations, procurement and product sourcing, sales, accounting, and advisory teams. 4) The development process of market-driving mechanisms consists of four main components: spatial mechanisms, social mechanisms, economic mechanisms, and external support mechanisms.